ANALYSIS INFLUENCE MIX MARKETING, QUALITY SERVICES AND DIGITALIZATION TO SATISFACTION PATIENTS AT NIRWANA GENERAL HOSPITAL BANJARBARU - Sari, Istiqamah Kiftiana; Agustina, Titien; Syamsuddinnor, Syamsuddinnor (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of the marketing mix, service quality, and digitalization on patient satisfaction at Nirwana General Hospital in Banjarbaru. This research is a quantitative study using descriptive analysis methods. The population was 37,490 outpatients. Using the Slovin formula, sample of 108 people. Data analysis technique using questionnaire with a Likert Scale. The data analysis technique uses multiple linear regression. Research results show that 1) Mix marketing influential significant to satisfaction patients at Nirwana Hospital Banjarbaru. 2) Quality service No influential significant to satisfaction patients at Nirwana Hospital Banjarbaru. 3) Digitalization No influential significant to satisfaction patients at Nirwana Hospital Banjarbaru. 4) Mixed marketing, quality services and digitalization in a way simultaneous influential significant to satisfaction patients at Nirwana Hospital Banjarbaru. Keywords: Marketing Innovation, Service Quality, Digitalization, Satisfaction Patient, Hospital